Support for students with additional health and developmental needs: practices and learnings from exemplar schools. Issue 2 (3rd July 2022) - Watts, Amy; Shingles, Beth; Edwards, Stuart; Goldfeld, Sharon
ABSTRACT: Students with additional health and developmental needs are at risk of poor psychosocial and academic outcomes as they enter and move through school. Early identification and supports to promote participation and learning can be highly effective in meeting the needs of these students helping them thrive academically, socially, and emotionally. This qualitative study aimed to learn from primary schools (n = 8) demonstrating exemplar practice in supporting students with additional health and developmental needs. Semi-structured interviews (n = 31) were conducted to explore how schools identify and monitor students, provide supports, and collaborate with stakeholders. Reflexive thematic analysis was used to analyse interview transcripts and a range of strategies and processes emerged that schools use inside and outside the classroom. The findings help to shape our understanding of potential exemplar practices for students with additional health and developmental needs within the primary school context and offer recommendations and practical opportunities for improvement.